Mechanism Optimization of Weight-Bearing Lower Extremity Exoskeleton based on Analysis of Multi Degree of Freedom - Chen Zhiqing; Cao Heng; Zhu Jun; Lü Rongan (Jixie chuandong)
In order to offset load torque,many weight- bearing lower extremity exoskeleton install gas spring in the hips which make the human walk abnormally in single leg support phase due to the disappearance of the rotation junction. To solve this problem,aiming at the exoskeleton robot " ELEbot" designed by east China University of Science and Technology,by using the screw theory,the " ELEbot" degrees of freedom and constraints in the single leg support phase are calculated and determined and then an improved mechanism to meet demand for degrees of freedom in this posture is put forward and the rationality of the drive configuration is verified. Through ADAMS software,the simulation analysis of the building model is carried out,This simulation come to the conclusion that the simulation result is consistent with the theoretical calculation,the feasibility of the optimization mechanism is proved.